Documentation and Localization of Force-mediated Filamin A Domain Perturbations in Moving Cells - Nakamura, Fumihiko (2014)
Endogenously and externally generated mechanical forces influence diverse cellular activities, a phenomenon defined as mechanotransduction. Deformation of protein domains by application of stress, previously documented to alter macromolecular interactions in vitro, could mediate these effects. We engineered a photon-emitting system responsive to unfolding of two repeat domains of the actin filament (F-actin) crosslinker protein filamin A (FLNA) that binds multiple partners involved in cell signaling reactions and validated the system using F-actin networks subjected to myosin-based contraction. Expressed in cultured cells, the sensor-containing FLNA construct reproducibly reported FLNA domain unfolding strikingly localized to dynamic, actively protruding, leading cell edges. The unfolding signal depends upon coherence of F-actin-FLNA networks and is enhanced by stimulating cell contractility. The results establish protein domain distortion as a bona fide mechanism for mechanotransduction in vivo.